The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/bcr.0000000000000156
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Young Adult Survivors of Pediatric Burns Using World Health Organization Disability Assessment Scale II and Burn Specific Health Scale-Brief

Abstract: Objective To determine long term psychological distress and quality of life (QOL) in young adult survivors of pediatric burns using the World Health Organization Disability Assessment Scale II (WHODAS) and the Burn Specific Health Scale- Brief (BSHS-B). Methods Fifty burn survivors 2.5–12.5 years post-burn (16–21.5 years old; 56% male, 82% Hispanic) completed the WHODAS and BSHS-B. The WHODAS measures health and disability and the BSHS-B measures psychosocial and physical difficulties. Scores were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 34 publications
2
13
0
3
Order By: Relevance
“…These figures show that burns are a major concern in the health area, because they can lead to an incapacitating condition accompanied by deep pain, and frequently, by long-term sequellae [3]. Functional outcome studies in pediatric burn populations confirm poorer levels of functioning associated with burn severity, face burns, lower appearance scores, and higher emotional and behavioral problems [4][5][6]. Costs for patients with burns are high as all domains of functioning can be affected, thus optimization of cost-effectiveness of burn care is needed [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…These figures show that burns are a major concern in the health area, because they can lead to an incapacitating condition accompanied by deep pain, and frequently, by long-term sequellae [3]. Functional outcome studies in pediatric burn populations confirm poorer levels of functioning associated with burn severity, face burns, lower appearance scores, and higher emotional and behavioral problems [4][5][6]. Costs for patients with burns are high as all domains of functioning can be affected, thus optimization of cost-effectiveness of burn care is needed [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…A recent review compares these two instruments in greater detail and found that they measure different concepts [32]. Past research using general health measures to infer quality of life have found that overall burn survivors are doing well [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…objective and subjective quality of life (Kikuchi et al, 2011). According to the World Health Organization"s definition of quality of life it is defined as an individual's perception of their position in life in the context of the culture and value systems in which they live (Murphy et al, 2015). In fact, it can be stated that an individuals" objectives, expectations, and wishes could influence his / her physical, psychological, and social condition and state (Holtan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%